(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
Comparative law has become an indispensable tool for legislators and judges who deal with issues related to biolaw. This paper offers a critical reflection on the importance that comparative law has gained with regard to the interpretation of the legislation in force and the drafting of new rules in the field of biolaw, taking into consideration the use of comparative law by the Court of Justice of the European Union, the European Court of Human Rights and the Italian Constitutional Court.